The first case of combined oxidative phosphorylation deficiency-1 due to a GFM1 mutation in the Serbian population: a case report and literature review - Aleksic, Dejan; Jankovic, Marina Gazdic; Todorovic, Stefan; Kovacevic, Marija; Borkovic, Milan (The Turkish Journal of Pediatrics, 2023)
Background. Combined oxidative phosphorylation deficiency-1 (COXPD1) resulting from a mutation in the G elongation factor mitochondrial 1 (GFM1) gene is an autosomal recessive multisystem disorder arising from a defect in the mitochondrial oxidative phosphorylation system. Death usually appears in the first weeks or years of lifespan. Case. We report a male patient with ventriculomegaly diagnosed in the 8th month of pregnancy. The delivery was done by caesarean section and respiratory failure occurred immediately after birth. Hypoglycemia, lactic acidosis, elevated gamma-glutamyl transferase and hepatomegaly were confirmed. The brain MRI detected hypoplasia of the cerebellar hemispheres, dilated lateral ventricles, and markedly immature brain parenchyma. Epilepsy had been present since the third month. At 5 months of age, neurological follow-up showed his head circumference to be 37 cm, with plagiocephaly, a low hairline, a short neck, axial hypotonia and he did not adopt any developmental milestones. A genetic mutation, a missense variant in the GFM1 gene, was confirmed: c.748C > T (p.Arg250Trp) was homozygous in the GFM1 gene. Conclusions. To the best of our knowledge, 28 cases of COXPD1 disease caused by mutations in the GFM1 gene have been described in the literature. COXPD1 should be considered due to symptoms and signs which begin during intrauterine life or at birth. Signs of impaired energy metabolism should indicate that the disease is in the group of metabolic encephalopathies.
Keywords: elongation factor G1; hepatoencephalopathy; lactic acidosis; mitochondrial disorder; mutation